Diplomacy and International Cooperation in ASEAN: An Analysis of Politics, Economy, and Law in Indonesia, Malaysia, Vietnam, Thailand, and Singapore - Liang, Ji (Journal of Comprehensive Science, 2024)
This article explores ASEAN's pivotal role in contemporary regional development and global change, focusing on politics, economics, and law in Indonesia, Malaysia, Vietnam, Thailand, and Singapore. ASEAN, as a major actor in state studies, offers theoretical innovations rooted in abundant empirical material, with diverse strategic outlooks and potential interactions. This research seeks to understand how ASEAN, through an interdisciplinary approach, utilizes the existing resources in Southeast Asian studies and the advantages of multidisciplinarity to build a dynamic, distinctive, and autonomous ASEAN studies. The article also discusses how the construction of ASEAN studies not only responds to contemporary propositions from regional and national studies, but also promotes the enhancement of global knowledge systems through systematic learning, research, and application practices. In addition, it evaluates current opportunities and challenges in the political, economic, and legal contexts of the five ASEAN countries mentioned earlier. The ultimate goal of this research is to help build a community of shared future for humanity by consolidating the intellectual foundation of the ASEAN community for a shared future.